2018
DOI: 10.5858/arpa.2017-0346-rs
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Nested Stromal-Epithelial Tumor of the Liver: An Update and Literature Review

Abstract: Calcifying nested stromal-epithelial tumor is a rare entity that has gone by a variety of names in the literature: ossifying malignant mixed epithelial and stromal tumor, ossifying stromal-epithelial tumor, and desmoplastic nested spindle cell tumor of the liver. To our knowledge, approximately 38 cases have been reported in the literature. The histogenesis is still largely unknown but histopathologically is characterized by nests of spindle and epithelioid cells in an organoid arrangement surrounded by a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The proposed PCM framework discussed in this study is uniquely suited to identify therapeutic alternatives even for rare cancers lacking actionable mutations and standard of care options. Calcifying Nested Stromal Epithelial Tumor (CNSET) is an exceptionally uncommon primary hepatic tumor that occurs in children and young adults, with only about 40 cases reported in the literature [36]. While localized disease is often effectively cured with surgical resection, recurrent and de novo metastatic disease demonstrates chemotherapy resistance and there are no proven therapeutic options [37][38][39][40].…”
Section: Pharmacotypes Identification For Clinical Trial Designmentioning
confidence: 99%
“…The proposed PCM framework discussed in this study is uniquely suited to identify therapeutic alternatives even for rare cancers lacking actionable mutations and standard of care options. Calcifying Nested Stromal Epithelial Tumor (CNSET) is an exceptionally uncommon primary hepatic tumor that occurs in children and young adults, with only about 40 cases reported in the literature [36]. While localized disease is often effectively cured with surgical resection, recurrent and de novo metastatic disease demonstrates chemotherapy resistance and there are no proven therapeutic options [37][38][39][40].…”
Section: Pharmacotypes Identification For Clinical Trial Designmentioning
confidence: 99%
“…There have been several cases of patients presenting with abdominal pain, mass, or Cushing syndrome. Liver function tests are most often normal without elevation of aminotransferases, bilirubin, or alkaline phosphatase [1]. Levels of tumor markers are similarly normal.…”
Section: Discussionmentioning
confidence: 99%
“…CNSET affects females to males in a ratio of 2.5:1 and most frequently involves the right hepatic lobe (65 % of cases) [1]. This tumor, as evidenced by review of the cases reported, appears to have a low malignant potential overall [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSET of the liver is an extremely rare, recently described nonhepatocytic, nonbiliary tumor of the liver. [1] In 2001, it was first described by Ishak et al [2] It is also called as desmoplastic nested spindle cell tumor of the liver and ossifying malignant mixed epithelial and stromal tumor. It consists of nests of the epithelial and spindle cells with associated myofibroblastic stroma and variable intralesional calcification and ossification.…”
Section: Discussionmentioning
confidence: 99%